(untitled) (REVISTA NODO, 2015)
This article is part of the research conducted in the doctoral thesis of the author and is currently subject of research at the University of La Salle. In this case, it has taken sustainable urban development seen from the perspective of the intermediate city in Latin America, a typology of town with features that go beyond its size , it refers more to the intermediary role that it meets within the region to which it belongs. In the beginning, the article discusses the problems that arise with urban growth and the impact it generates, also, the role of intermediate cities in the phenomenon of urban concentration. The features, benefits and challenges of intermediate cities are presented. They talk about the urgency of change of approach required for understanding the city as a system, likewise, sustainable urban development strategies and their characteristics are presented . Finally , the Proposal for the Sustainability of the City Intermediate PSCI is explained by its seven ( 7) criteria: Brokerage , Compactness , Efficiency , Livability , Mobility, Governance, and Citizen Participation ; and the most relevant conclusions.